Analysis of the Drama 'Orang-Orang Setia' by Iswadi Pratama as the Initial Work of an Actor - Syahputra, Andi; Susandro, Susandro; Sari, Dian Permata (Institut Seni Indonesia Padangpanjang, 2023)
The presentation of Rahman's character in Iswadi Pratama's drama Orang Setia uses Stanislavsy's acting method which he calls the system. Stanislavsky's system is an acting method created to understand characters scientifically so that they can be presented by actors on stage. In Stanislavsky's acting method, there are three parts that he calls the